2020
DOI: 10.1177/0003489420922862
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Intervention for Laryngomalacia: Age-Related Differences in Postoperative Sequelae

Abstract: Objective: Identify risk factors and determine perioperative morbidity of children undergoing surgery for laryngomalacia (LM). Methods: A retrospective analysis of the multi-institutional American College of Surgeons National Surgical Quality Improvement Program-Pediatric Database (ACS-NSQIP-P) was performed to abstract patients aged <18 years with LM (ICD-10 code Q31.5) who underwent laryngeal surgery (CPT code 31541) from 2015 to 2017. Analyzed clinical variables include patient demographics, hospital set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
1
0
0
Order By: Relevance
“…As a preoperative means of assessing surgical risk, elevated ASA class had previously been implicated in prolonging hospitalization in pediatric patients who underwent supraglottoplasty. 20 Therefore, it is no surprise that our study also showed ASA class greater than or equal to 3 is a strong predictive factor of extending LOS. This finding can be interpreted as a surrogate measure of the severity of baseline comorbidity.…”
Section: Length Of Staysupporting
confidence: 57%
“…As a preoperative means of assessing surgical risk, elevated ASA class had previously been implicated in prolonging hospitalization in pediatric patients who underwent supraglottoplasty. 20 Therefore, it is no surprise that our study also showed ASA class greater than or equal to 3 is a strong predictive factor of extending LOS. This finding can be interpreted as a surrogate measure of the severity of baseline comorbidity.…”
Section: Length Of Staysupporting
confidence: 57%